Identifying Light Verb Constructions in Indonesian: A Direct Translation Approach: A DIRECT TRANSLATION APPROACH - Nugraha, Danang Satria (International Journal of Language and Literary Studies, 2022)
This study aimed to identify light verb constructions (LVCs) in Indonesian based on machine translation methods, namely binary translation or direct translation. Based on the method, the LVCs of the source language (SL) were selected and utilized to construct the LVCs counterpart of the target language (TL). The SL instrument has been developed using previous studies on English and Hungarian, namely the LVCs matrix formulated by Vincze (2011). The TL data were in the equivalent forms of LVCs in Indonesian. Data analysis was carried out based on morphosemantics and morphosyntax. Based on the study, the result was stated as follows, i.e. (i) there were translation work procedures that needed to be carried out to process LVCs from SL to TL regarding the type of translator, limited text selection, and final counterpart assignation; (ii) there were changes in the morphosemantic features of LVCs from SL to TL during the translation process; and (iii) there were grammatical exceptions that cannot be resolved through binary translation methods. This study also suggested a further analysis of LVCs identification through another method, for instance, information retrieval (IR) and information extraction (IE), in the light of computational linguistics.